2002
DOI: 10.1126/science.1069434
|View full text |Cite
|
Sign up to set email alerts
|

Operant Reward Learning in Aplysia : Neuronal Correlates and Mechanisms

Abstract: Operant conditioning is a form of associative learning through which an animal learns about the consequences of its behavior. Here, we report an appetitive operant conditioning procedure in Aplysia that induces long-term memory. Biophysical changes that accompanied the memory were found in an identified neuron (cell B51) that is considered critical for the expression of behavior that was rewarded. Similar cellular changes in B51 were produced by contingent reinforcement of B51 with dopa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
275
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(296 citation statements)
references
References 31 publications
14
275
0
3
Order By: Relevance
“…[12,33,40,45]) and, furthermore, supported the hypothesis that such studies may tap into fundamental neurobiological alterations that underlie drug addictions [7,33,58,65]. It demonstrated that a psychostimulant drug of abuse could be rewarding to an animal that, unlike mammalian species, exhibits a relatively simple neuronal organization.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[12,33,40,45]) and, furthermore, supported the hypothesis that such studies may tap into fundamental neurobiological alterations that underlie drug addictions [7,33,58,65]. It demonstrated that a psychostimulant drug of abuse could be rewarding to an animal that, unlike mammalian species, exhibits a relatively simple neuronal organization.…”
Section: Discussionmentioning
confidence: 59%
“…Electrical stimulation [5], biogenic amines [40] or food items [45] have served as rewards in past studies of invertebrates and in some cases there has since been considerable advance into understanding the underlying proximate mechanisms of such processes (e.g., ref. [12]). A recent study, where planarians were conditioned to prefer environments associated with methamphetamine treatments, was a notable exception to the general lack of explicit studies of drug reward in invertebrate taxa [33].…”
Section: Introductionmentioning
confidence: 99%
“…The impairment produced by PCP, a glutamatergic antagonist, correlates significantly with a decrease in DA levels only in the DLPC and in the prelimbic cortex, and is reversed by clozapine. Brembs et al, (2002) have demonstrated in Aplysia a cellular model of DA enhanced instrumental conditioning.…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
“…Recent studies suggest the involvement of DA activity in some of the circuits that are associated with the behavioral dimensions of BPD. For example, it has been suggested that the Aplysia cellular model of DA-enhanced instrumental conditioning recently demonstrated by Brembs et al (2002) may be conserved in higher animal forms, and may provide the basis for the learning of reward-seeking behaviors mediated by DA in the NAC (Rankin, 2002).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Recording extracellularly from the esophageal nerve in the intact animal during a biting movement that fails to grasp food reveals little activity. However, when the animal grasps and swallows seaweed, there are bursts of activity in the esophageal nerve during and outlasting the swallowing movements [30 ]. Presumably, the esophageal nerve transmits information about the presence of food to the buccal ganglia.…”
Section: Operant Reward-learning Of Feeding Behavior In Aplysiamentioning
confidence: 99%